ON CHIP MEMORY REDUCTION TECHNIQUE FOR DATA DOMINATED EMBEDDED SYSTEMS - Chepure, Srilatha; Rao, Guru C.V.; Benakop, Prabhu G. (International Journal of Computing, 2014)
This paper proposes an approach for optimization of on-chip memory size in data dominated embedded systems. Large amount of array processing is being involved in this category. In order to produce a cost effective system, efficient designing of memory module is quite critical. The memory module configuration being selected by the designer should be well suitable for the application. In this regard, this paper presents a methodology for effective optimization of on-chip memory. For sensitive applications involving large array processing, the entire processing has to be done using embedded modules. While using such module s, care should be taken to meet optimized profile for the design metrics. With help of loop transformation technique, relatively a good amount of memory size requirement is reduced for the arrays. This approach results in a very close memory estimate and an effective optimization. This methodology can be further extended to meet the high level memory optimization applications based on cache characteristics. Speech processing front end mechanism is implemented and shows that this approach gives up to an achievement 61.3% reduction of overall system memory requirement over the estimation approach. Results are provided in terms of comparison of the two approaches of memory estimation and optimization with respect to both of the program and data segments.